Energy and exergy analysis of the steam power plants: A comprehensive review on the Classification, Development, Improvements, and configurations - Khaleel O.J.; Basim Ismail F.; Khalil Ibrahim T.; bin Abu Hassan S.H. (Ain Shams University, 2023)
Boilers; Coal combustion; Exergy; Feedwater heaters; Fossil fuel power plants; Quality control; Steam; Steam power plants; Comparative evaluations; Complex task; Energy; Energy and exergy analysis; Energy systems; Operation conditions; Optimum energy; Quality of energies; Thermal-power plants; Thermodynamic systems; Thermoelectric power plants